International Student Spouses and the English Language: Co-Creating a Low Stakes Language Learning Community - Grimm, Adam Thomas; Kanhai, Dana; Landgraf, Jessica (Journal of International Students, 2019)
In the context of the internationalization of U.S. higher education, millions of international students have come to study at U.S. institutions. Some students, particularly those pursuing advanced degree, bring their spouses. As part of a larger study, we set out to examine the experiences of international student spouses at a Midwestern university. This article examines the experiences from the perspective of grappling with the English language, a theme cross-cutting through spouses’ experiences. Experiences with English, the focus of this article, are both a discrete element of spouses’ lived experiences and a useful way to understand challenges and opportunities not directly related to language. Utilizing qualitative case study techniques, we found that English language is experienced through anxieties as well as ambitions by the participants in our study.